2013
DOI: 10.1371/journal.pone.0055189
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Survey of Work Environment, Work-Life Balance and Burnout among Psychiatrists in Japan

Abstract: BackgroundPsychiatry has been consistently shown to be a profession characterised by ‘high-burnout’; however, no nationwide surveys on this topic have been conducted in Japan.AimsThe objective of this study was to estimate the prevalence of burnout and to ascertain the relationship between work environment satisfaction, work-life balance satisfaction and burnout among psychiatrists working in medical schools in Japan.MethodWe mailed anonymous questionnaires to all 80 psychiatry departments in medical schools t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 44 publications
5
38
1
2
Order By: Relevance
“…In our study, psychiatrists suffered from depression, burnout, and anxiety more often than other doctors. Low social support is a major predictor of occupational stress in doctors and nurses (Wu, Ge, Sun, Wang, & Wang, 2011;Wu, Zhao, Wang, & Wang, 2010); particularly in psychiatrists, high levels of social support are most strongly associated with low levels of poor mental health (Umene-Nakano et al, 2013). Receiving social support for work-related problems reduces work-related exhaustion and increases mental energy in psychiatrists (Shailesh, Simon, Gaelle, Jesse, & Etuini, 2011).…”
Section: Implications For Program Improvement In Chinamentioning
confidence: 99%
“…In our study, psychiatrists suffered from depression, burnout, and anxiety more often than other doctors. Low social support is a major predictor of occupational stress in doctors and nurses (Wu, Ge, Sun, Wang, & Wang, 2011;Wu, Zhao, Wang, & Wang, 2010); particularly in psychiatrists, high levels of social support are most strongly associated with low levels of poor mental health (Umene-Nakano et al, 2013). Receiving social support for work-related problems reduces work-related exhaustion and increases mental energy in psychiatrists (Shailesh, Simon, Gaelle, Jesse, & Etuini, 2011).…”
Section: Implications For Program Improvement In Chinamentioning
confidence: 99%
“…High burnout is defined as an emotional exhaustion score of 27 points or higher, depersonalization score of 10 points or higher, and personal accomplishment score of 33 points or lower 12 . The reliability and validity of the Japanese version of Maslach Burnout Inventory have been proven in several references 10,13,14 .…”
Section: Questionnairementioning
confidence: 99%
“…If the current study utilized the same term found in the research literature, then the variable name is typed in bold without brackets. QWL has been connected to job performance (techniques), turnover, interpersonal skill commitment (commitment), client adherence (dropouts), client outcomes (successful outcomes), work schedules (monthly NFB sessions), career satisfaction (years of NFB experience), and burnout (Bragard, Dupuis, Razavi, Reynaert, & Etienne, 2012;Erdogan, Bauer, Truxillo, & Mansfield, 2012;Firth-Cozens, 2001;Larson, Ryan, & Baerentzen, 2010;Larson, Cothran, Drandorff, Morgan, & Ryan, 2012;Maslach, Schaufeli, & Leiter, 2001;Page & Vella-Brodrick, 2012;Sirgy, Reilly, Wu, & Efraty, 2008;Umene-Nakano et al, 2013). The current paper investigates calmness, confidence, observant, realistic, and optimistic because practitioners reported the importance of these traits within NFB settings (Larson, Ryan, & Baerentzen, 2010;Larson et al 2012).…”
Section: Study Rationalementioning
confidence: 99%
“…Research has demonstrated that limited resources, increased role diffusion, increased work demands, burnout, work schedules, reduced employee support, and work stress negatively impact Quality of Work Life (QWL) (Bragard, Dupuis, Razavi, Reynaert, & Etienne, 2012;Maslach, Schaufeli, & Leiter, 2001;Sirgy, Reilly, Wu, & Efraty, 2008;Umene-Nakano et al, 2013). A systematic literature review revealed that career satisfaction, job performance, organizational commitment, quality of work life, and turnover intentions are related to life satisfaction (Erdogan, Bauer, Truxillo, & Mansfield, 2012).…”
Section: Introductionmentioning
confidence: 99%